G273(P) Successes and challenges of introducing clinical job aides in district hospitals in myanmar. (12th March 2018) - Halbert, J; Malley, M; Monaghan, M; Roche, E; Babu, P; Oo, S; Bowyer, J; Wooton, M; Sin, KT
Abstract : Aims: Clinical job aides directly benefit clinical care and assist project evaluation. We describe early experience of their introduction as part of an Emergency Paediatric Care Programme (EPCP). Methods: An EPCP working group developed pilot job aides. These included admission, observation and drug charts that were piloted in 11 hospitals. Between May and October 2016 the job aides were reviewed and a survey of local healthcare workers undertaken. Results: In the majority of hospitals job aides were limited or inadequately completed. Vital sign charts typically only recorded the temperature. The prescription and administration of drugs were recorded in separate places, and admission information recorded on a brief proforma. Although the job aides received positive endorsement during the EPCP courses there has been some resistance to their use in the wards. A survey of patient notes at one site demonstrated that no staff were using the admission forms or the drug charts adequately. Vital signs charts were more acceptable and 100% were satisfactory. Healthcare workers considered the job aides useful, but cited poor staffing and lack of time as the reason for limited acceptance. Suggestions included: Senior endorsement Training for all staff on how to use the job aides Explanation to nurses how vital signs charts can be used to monitor patient progress and signal when to get help Conclusion: Job aides can focus the attention of healthcare workers on key signs and symptoms as taught in EPCP. Ongoing training, familiarisation, mentorship and support from senior colleagues will be key for their successful introduction.